MoS2/Reduced Graphene Oxide-Based 2D Nancomposites for Boosting the Energy Density of Electric Double-Layer Capacitor. Issue 22 (19th February 2016) - Manoharan, Anishkumar; Tian, Z. Ryan; Ang, Simon S.
ABSTRACT: A method for synthesizing and structuring 2D-MoS2 /rGO (molybdenum disulfide/reduced graphene oxide) nanocomposite-based electric double layer capacitor (EDLC) that has a slower discharge rate and higher energy density than rGO-based EDLC (RG-EDLC) is reported. The rGO electrode and the nanocomposite were characterized using powder XRD and SEM for their physical and structural properties. Cyclic voltammetry (CV) was used to analyze the electrochemical behavior of the EDLCs. A maximum current density at which the MoS2 /rGO nanocomposite-based EDLC (MRG-EDLC) can charge and discharge was 2.5 A/g, while it was 1A/g for the RG-EDLC. The specific capacitance of the MRG-EDLC was 14.52 F/g at 0.5 A/g with an energy density of 8.06 Wh/kg.